ANALYSIS OF SCHOOL MANAGEMENT IN REALIZING QUALITY CULTURE IN MADIUN CITY - Lismawati Lismawati; Rudi Handoko; Rachmawati Novaria (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
The implementation of the school management system has a strategic role in supporting the implementation of public services at the education unit level. The role and function of supervision are needed to monitor, foster, assess, and provide professional guidance to principals, teachers, and education personnel in their target schools. The phenomenon in the field shows a gap in the quality standards of education set by the government and its implementation. No school has met the SNP of the 71 primary schools in Madiun City. This research was conducted because elementary schools in Madiun City do not yet have a quality culture according to the standards set by the government. This study aims to: a. Describe and analyze school management in realizing a quality culture. b. Analyze the factors inhibiting and supporting school management in realizing a quality culture. c. Develop a management model that can encourage a quality culture. The study was conducted qualitatively. The results of the study are as follows; a. The management of elementary schools in Madiun City has met the criteria for quality culture, but at the implementation level, it is not optimal. It can be seen that school management is not optimal, so the quality culture has not been realized as expected by the government. b. Supporting factors, schools are committed to implementing SPMI towards quality cultured schools following applicable regulations, supported by educators and education staff who have the appropriate qualifications. Provisions, a management information system, and the availability of special officers.